Book Review (AmeriQuests, 2017)
Review of A Hope More Powerful Than the Sea: One Refugee's Incredible Story of Love, Loss, and Survival, by Melissa Fleming (Flatiron Books, 2017), $13.68 (hardcover), 288 pages, ISBN: 978-1250105998